Hubungan Penguasaan Perbendaharaan Kata Anak Usia Taman Kanak-Kanak dengan Aktivitas Menonton Televisi: The Relationship Between Vocabulary Mastery in Kindergarten-Aged Children and Television Watching Activities - Muhammad Ali Makki (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
Kindergarten-aged children are in a sensitive period for personality development. During this time, several personalities begin to form, and the differences in each child's personality become more apparent. Abilities that develop rapidly during this period include physical and language skills. To enhance vocabulary mastery in kindergarten-aged children, several related factors include cultural and family background, family living standards, parental education levels, and family location. Other factors associated with vocabulary acquisition in children include mother-child interaction, storytelling activities, and imitation (mimesis). Television watching activities are considered highly influential on the number of vocabulary acquisitions in kindergarten-aged children. This means that the more children watch television, the more vocabulary they acquire. Television programs can positively impact vocabulary acquisition in kindergarten-aged children. Through television, children can learn and imitate new words. Anak usia taman kanak-kanak (TK) merupakan masa peka bagi perkembangan kepribadian anak. Pada masa ini, beberapa kepribadian mulai terbentuk, dan perbedaan kepribadian setiap anak semakin jelas terlihat. Kemampuan yang terbentuk dan berkembang pesat pada masa ini meliputi perkembangan fisik dan kemampuan berbahasa. Sebagai upaya untuk meningkatkan penguasaan perbendaharaan kata pada anak usia TK, beberapa faktor yang terkait antara lain latar belakang budaya dan keluarga, taraf hidup keluarga, tingkat pendidikan keluarga, serta lokasi keluarga. Faktor lain yang juga berhubungan dengan pemerolehan perbendaharaan kata pada anak meliputi interaksi ibu dan anak, aktivitas mendengarkan cerita, dan faktor imitasi (mimesis). Aktivitas menonton televisi dianggap sangat berpengaruh terhadap jumlah perbendaharaan kata yang dikuasai anak usia TK. Artinya, semakin sering anak menonton televisi, semakin banyak perbendaharaan kata yang dimilikinya. Tayangan televisi dapat memberikan pengaruh positif terhadap pemerolehan perbendaharaan kata anak usia TK. Melalui televisi, anak dapat memperoleh dan meniru kata-kata baru.